A systematic review comparing urban flood management practices in India to China’s sponge city program - Kumar, N.; Liu, X.; Narayanasamydamodaran, S.; Pandey, K.K. (MDPI AG, 2021)
India and China are among the two most populous countries in the world that concomitantly incur substantial flood-related losses, and both countries are also experiencing rapid urbanization. This study was conducted to trace the major urban flooding cases in these countries between 2014 and 2020 and probe into their existing flood mitigation policies with special focus on China’s Sponge City Program (SCP). A systematic review using preferred reporting items for systematic review and meta-analysis protocols (PRISMA) was conducted. Results showed that both these countries experienced comparable challenges in terms of the need for localized low impact development (LID) planning given their extensive geographically induced diversities. Improved inter-governmental and inter-agential coordination, new avenues of funding involving public and private enterprises with accommodations to source local products and services to boost local economies, improved practical and technical understanding for working professionals and improved community acceptance and participation are also recommended. It is concluded that India should try to focus on holistic urban water resilience as China does with its Sponge City Program and that China should take a cue from India’s contractual and tender-based private service sourcing methods to tide over its financial setbacks in order to achieve its ambitious targets for 2030. © 2021 by the authors.
Keywords: urban flooding; sponge city; smart city; low impact development; runoff